Status, Challenges, and Prospects of Aquaculture Development in Iraq - AL-Hilali, Hasan (Iraqi Journal of Aquaculture, 2025)
Aquaculture in Iraq has undergone significant development, transforming from rudimentary practices to modern systems that support food security and economic growth. This sector has shown resilience despite facing numerous challenges, including water scarcity, environmental pollution, Political instability, and limited technological resources. Historically, aquaculture production in Iraq has been dominated by carp species, cultivated primarily in earthen ponds and floating cages using deferent agriculture methods. While production has seen periods of growth, such as the adoption of artificial propagation techniques and the rise of private sector involvement, it has also experienced setbacks due to political and economic instability, as well as external environmental factors. Currently, aquaculture contributes nearly 95% of Iraq's total fish production, making it a vital component of the nation's food system. However, constraints like deteriorating water quality, inefficient farming practices, and limited access to advanced technology hinder sustainable growth. This review provides an in-depth analysis of the historical progression, current state, and challenges facing the aquaculture industry in Iraq. Additionally, it explores opportunities for advancing sustainable aquaculture through the adoption of modern technologies, improved resource management, and policy reforms. The findings aim to guide future strategies to enhance aquaculture's contribution to food security, Luxury living, and environmental sustainability in Iraq.